2018
DOI: 10.1108/ebr-02-2017-0034
|View full text |Cite
|
Sign up to set email alerts
|

Electronic marketing orientation in the Small and Medium-sized Enterprises context

Abstract: Purpose There is an increasing interest in the role of business orientations in relation to why organizations vary in e-marketing adoption. Nevertheless, there is still scant evidence on electronic marketing orientation (EMO) within the Small and Medium-sized Enterprise (SMEs) context. This paper aims to shed light on the key factors that affect the degree of e-marketing adoption among SMEs from an organizational orientation perspective. Design/methodology/approach The study uses a cross-sectional survey of j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 34 publications
0
14
0
12
Order By: Relevance
“…It was also concluded that this interactive ICT medium made it possible to reach potential customers outside their traditional trading footprint than would be possible with traditional communication media (Bocconcelli et al, 2017;Ahmad et al, 2018;Ntshingila, 2020;Steel, 2021). Given that half of the world's population are active social media users (Kemp, 2020), familiarity with the different social network platforms made it easier for the respondent retailers to engage and interact with customers on these platforms (Shaltoni et al, 2018). This illustrates the possible benefits through the accessibility of social media in both the emerging and developed markets.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was also concluded that this interactive ICT medium made it possible to reach potential customers outside their traditional trading footprint than would be possible with traditional communication media (Bocconcelli et al, 2017;Ahmad et al, 2018;Ntshingila, 2020;Steel, 2021). Given that half of the world's population are active social media users (Kemp, 2020), familiarity with the different social network platforms made it easier for the respondent retailers to engage and interact with customers on these platforms (Shaltoni et al, 2018). This illustrates the possible benefits through the accessibility of social media in both the emerging and developed markets.…”
Section: Discussionmentioning
confidence: 99%
“…Its general use by customers and businesses means that it is an accessible online ICT medium through which to communicate with current and potential customers. Facebook was highlighted as a platform with which the respondents were familiar, which facilitated its accessibility (Rootman, 2016;Crammond et al, 2018;Shaltoni et al, 2018). This sentiment was reflected by most of the respondents.…”
Section: Reachmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our current understanding on market orientation is not adequate to fully capitalise with the concept of market orientation in order to explore further market opportunities (Shaltoni et al, 2018). Understanding the transnational stakeholders' varied contexts would be useful for TNEs to recognise the suitable scope and extent of strategic market orientation, and engaging the transnational stakeholders to co-create value that could contribute to the growth of a TNE and the associated transnational stakeholders (Christofi et al, 2018;Vrontis et al, in press).…”
Section: Transnational Education Stakeholders Stakeholder Causal Scomentioning
confidence: 99%